2008
DOI: 10.1016/j.bar.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing strategy, broad scope MAS information and information and communication technology

Abstract: In today's global business environment, firms are under pressure to create competitive advantages. Among the ways to do so are offering a wide range of quality products at competitive price and being customer responsive. The pressure also acts as an impetus for firms to employ strategies suitable for creating competitive advantages. Just-in time manufacturing (JIT) is one such strategy. This study tested the proposition that the relationship between a firm's successful JIT application and its managers' use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 29 publications
8
42
0
1
Order By: Relevance
“…This finding is consistent with previous researches (e.g. Mia, 2000;Mia and Winata, 2008). It means that if managers use more non-financial, external, future oriented, timely and aggregated information that are provided by MAS, the higher the chances of meeting their performance targets.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with previous researches (e.g. Mia, 2000;Mia and Winata, 2008). It means that if managers use more non-financial, external, future oriented, timely and aggregated information that are provided by MAS, the higher the chances of meeting their performance targets.…”
Section: Discussionsupporting
confidence: 92%
“…First, the sample population of this study was narrowly focused on Iranian financial organizations and may not be a true representation of all Iranian industries. Second, this study uses a selection of constructs (contingent variables) based on previous literature like: Hoque (2011), Mia and Winata (2008), Chung et al (2012) and Etemadi et al (2009). It is possible that there are other important constructs that can affect MAS and managerial performance.…”
Section: Discussionmentioning
confidence: 99%
“…He also proposes that the advanced technologies of JIT are associated with broadly based MCS. Mia and Winata (2008) found that JIT is positively associated with the use of broad scope MAS information. Ahmad and Mohamed Zabri (2015) revealed that AMT has a positive association with the use of costing system, performance evaluation system and strategic management accounting.…”
Section: Lean Manufacturing Mas Information and Performancementioning
confidence: 94%
“…Year Application Techniques Mia and Winata (2008) Revealed that JIT application is positively associated with managers' use of broad scope information provided by the management accounting system (MAS information), which in turn, is positively associated with the use of ICT. Simulated annealing (SA), kanban Panayiotou and Cassandras (1999) Developed an algorithm to maximise the throughput of a kanban manufacturing system with arbitrary arrival and service process distributions by adjusting the number of kanban allocated to each production stage while maintaining the total work-in-process inventory at any desired level.…”
Section: Authormentioning
confidence: 98%